(untitled) (Journal of Pathology of Nepal, 2025)
Background: Lymphomas are a group of heterogeneous lymphoproliferative malignancies with a distinctive behavior and treatment responses. Immunohistochemistry guides the accurate subtyping, diagnosis, and prognostication of lymphomas. The objective of this study was to observe subtypes of lymphoma and their distribution and frequency by age and gender. Materials and Methods: A two-year retrospective study (2020-2022) was conducted in the Department of Pathology, Vydehi Institute of Medical Sciences and Research Centre, India. Cases were subcategorized using panels of Immunohistochemistry. Results: Of 100 lymphoma cases, 73 were Non-Hodgkin lymphoma and 27 Hodgkin lymphoma. Males outnumbered females in both groups. Among NHL, Diffuse Large B-Cell Lymphoma-Not Otherwise Specified comprised 56%, with 29% being anaplastic variant, followed by small lymphocytic lymphoma. In Hodgkin Lymphoma, 25 cases were Classical Hodgkin Lymphoma, and 2 were Nodular Lymphocyte Predominant Hodgkin Lymphoma. Nodal involvement was more frequent, 73.6% in Non-Hodgkin Lymphoma and 85.1% in Hodgkin Lymphoma, with the cervical lymph node most commonly affected. Extranodal disease accounted for 27.3% of Non-Hodgkin Lymphoma and 14.8% of Hodgkin Lymphoma. Conclusions: Non-Hodgkin Lymphomas predominated over Hodgkin Lymphoma, with Diffuse large B-cell Lymphoma-NOS being the most common subtype. Immunohistochemistry remains essential for precise lymphoma subclassification, ensuring accurate diagnosis.